KAJIAN KUALITAS PELAYANAN BERDASARKAN ISO 9001:2000 CLAUSE 8: STUDI KASUS PADA INSTALASI FARMASI RSUD PROF. DR. MARGONO SOEKARJO - Wiwiek Rabiatul Adawiyah (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2007)
The study entitled An Analysis on Service Quality Based on ISO 9001: 2000 Clause 8 is aimed at evaluating the quality of service provided by Installation of Pharmacy at Prof Dr. Margono Soekarjo Hospital. The tools used for analysis are statistical quality control (SQC). Among the tools used are check sheet, pareto diagram, fishbone diagram, and control chart. The Data was analyzed by comparing the length of timerequired to serve customers, before and after process improvement. The conclusion obtained are: first, there has been improvement in the length of time required to serve customer from 75,8 to 41,2 minutes; second, the used of statistical quality control are efficient and effective in controlling the service quality at the Pharmaceutical Installation; Third, Control Chart is very useful for determining the specification line for the purpose of controlling; finally, Quality Circle members must continuously be educated on the tools used in ISO 9001: 2000 in order to improve work performance.